1999
DOI: 10.1017/s026646239915414x
|View full text |Cite
|
Sign up to set email alerts
|

Using Telehealth Interventions to Prevent Pressure Ulcers in Newly Injured Spinal Cord Injury Patients Post-Discharge

Abstract: Objective: To determine which of three approaches to care produces the lowest incidence of pressure ulcers, promotes the most effective care of sores that develop, and leads to the fewest hospitalizations in newly injured patients with spinal cord injury after discharge.Methods: Spinal cord injury patients (n = 12) were recruited for a telehealth intervention after initial injury, and matched cases were recruited for telephone counseling and standard care groups. Patients were monitored for 6–8 months af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 8 publications
1
37
0
Order By: Relevance
“…Nevertheless, even in a small study sample with a short followup period, we demonstrated significantly improved functional status indicators and very high participant support of home-based physical telerehabilitation. Based on our analysis of previous literature [54][55][56][57][58][59][60], the magnitude of change demonstrated in our study after a 12-week follow-up apparently exceeds previously reported potential practice effects. To convincingly and objectively document the clinical benefits of physical telerehabilitation and to avoid possible biases, researchers should use a randomized controlled trial design.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Nevertheless, even in a small study sample with a short followup period, we demonstrated significantly improved functional status indicators and very high participant support of home-based physical telerehabilitation. Based on our analysis of previous literature [54][55][56][57][58][59][60], the magnitude of change demonstrated in our study after a 12-week follow-up apparently exceeds previously reported potential practice effects. To convincingly and objectively document the clinical benefits of physical telerehabilitation and to avoid possible biases, researchers should use a randomized controlled trial design.…”
Section: Discussionsupporting
confidence: 45%
“…Although physical telerehabilitation systems are actively used in treating patients with other neurological conditions, such as stroke [54][55][56] or spinal cord injuries [57][58], experience using them in treating patients with MS is limited. One approach described by Egner et al uses videoconferencing or conventional telephone calls [59].…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to identify the incidence of pressure ulcers in community dwelling wheelchair users because self-reporting often leads to substantial underreporting (Phillips, Temkin, Vesmarovich, Burns, & Idleman, 1999). Pressure ulcers can be accurately diagnosed via telephone and/or video conference interactions between care providers and patients (Hill, Cronkite, Ota, Yao, & Kiratli, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Pressure ulcers can be accurately diagnosed via telephone and/or video conference interactions between care providers and patients (Hill, Cronkite, Ota, Yao, & Kiratli, 2009). If conducted regularly these interactions have been shown to help with early diagnosis (Phillips et al, 1999). However, regularly interacting with every wheelchair user via telephone is not feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Within the neurological disability population, a randomized trial of recently hospitalized spinal cord injury patients showed that weekly telephone (n = 36) or videoconference visits (n = 36) with a rehabilitation nurse improved oneyear health outcomes, as compared to a control group (n = 39) receiving "usual care" [49] and a randomized controlled trial of 81 patients with stroke, brain injury or multiple sclerosis found similar improvements in arm/hand function outcomes between a group receiving a six-month long telerehabilitation intervention and those receiving face-to-face outpatient care [30]. Pilot studies involving people with stroke [41], brain injuries [44,55,63], multiple sclerosis [20], Parkinson's disease [22] and spinal cord injury patients at risk for pressure ulcers [48] suggest that the telehealth component of smart home technology holds promise to reduce health care costs and improve disability outcomes.…”
Section: Efficacy and Outcomes Researchmentioning
confidence: 99%